Analyzing Russian Media Policy on Promoting Vaccination and Other COVID-19 Risk Mitigation Measures - Stepanov, Ivan; Komendantova, Nadejda (Frontiers in Public Health, 2022)
The COVID-19 pandemic has resulted in many tangible and intangible losses. To manage the risk of the pandemic and mitigate its further spread, the governments of many countries applied various pandemic risk mitigation measures. Media campaigns played a particularly large role during the pandemic too. In addition, social media grew in importance due to the spread of technologies as well as in result of the increased attention to information about COVID-19. Media information strongly influenced both the public perception of COVID-19 risk and the decision-making process and choices, which people made regarding risk reduction measures during the pandemic. Moreover, media information has had a major impact on the effectiveness and efficiency of various countries’ risk management actions. Therefore, the purpose of this paper is to investigate the influence of the Russian media on the population’s perception of risk and which linguistic and psychological methods they used to shape different media discourses about the COVID-19 pandemic. Thus, we analyzed media discourses as part of a case study of COVID-19 risk management in the Russian Federation. The theoretical basis of the study includes the mass communication theories, and the methodological basis consists in linguo-cognitive analysis of empirical materials for specific political-philosophical, linguistic-publicistic and socio-psychological functioning.